A rare pituitary tumor associated with hyperthyroidism and acromegaly - Li, Li; Meng, Liheng; Liu, Yuping; Tamrakar, Rashi; Yang, Xi; Liang, Xinghuang; Zhou, Jia; Xian, Jing; Huang, Zhenxing; Qin, Yingfen (Frontiers in Endocrinology, 2022)
Background: Mixed pituitary TSH/GH adenomas are rare adenomas associated with acromegaly and/or thyrotoxicosis, with or without varying degrees of goiter. In this report, we show a case of pituitary adenoma producing both GH and TSH simultaneously. Case presentation: A 27-year-old man was diagnosed as pituitary adenoma based on various symptoms and clinical findings. For further examination and treatment, he was hospitalized in our institution. It was likely that this subject had pituitary adenoma producing both GH and TSH. In brain magnetic resonance imaging, there was a giant tumor in the sellar region. After the diagnosis of mixed pituitary TSH/GH adenoma, he was treated with octreotide, then underwent tumor resection, and then received hydrocortisone acetate and levothyroxine sodium. After then, GH and IGF-1 levels were suppressed, and thyroid function was normalized. Postoperative immunohistochemistry reports showed GH(+) but TSH(-), which may be insensitive to the antibody used to detect TSH or combined with other factors. Conclusions: The diagnosis of mixed pituitary TSH/GH adenoma must be combined with clinical manifestations, immunohistochemical staining and relevant hormone levels, and genetic testing if necessary for comprehensive judgment. For patients with large adenomas, it is recommended to use somatostatin analogs to restore TH levels and control the excessive secretion of GH levels before surgery.